Visualization of the epimysium and fascia thoracolumbalis at the lumbar spine using MRI - Adamietz, Boris; Schönberg, Stefan; Reiser, Maximilian; Uder, Michael; Frank, Andreas; Strecker, Ralph; Weiß, Christel; Heiss, Rafael (Der Radiologe, 2021)
The fascia thoracolumbalis (FTL) is an important component for stabilization and motion control of the lumbar spine. It coordinates the traction forces of the autochthonous muscles of the back (AM) and connects them to the muscles of the abdominal wall, shoulder, and buttocks.